Climate Change and Non-Infectious Fish Disorders 2019
DOI: 10.1079/9781786393982.0136
|View full text |Cite
|
Sign up to set email alerts
|

Stress in response to environmental changes.

Abstract: This chapter discussed environmental factors that are affected by climate changes in influencing the endocrine stress response in fishes. It has also recently been reported from previous studies that the exposure of parents to environmental changes may improve progeny survival in fish, implicating epigenetics as a mechanism for long-term and generational adjustments to environmental stressors.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
7
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(7 citation statements)
references
References 0 publications
0
7
0
Order By: Relevance
“…The net result of those would depend on the severity of the sustained stressor, but they can have consequences that extend to fish populations (Adams, 1990; Barton, 2002). In addition, prolonged exposure to stress and changes in circulating corticosteroids (mainly cortisol) may have long‐lasting effects on the stress physiology of the organism that influence the coping ability of their progeny (Colson et al ., 2015, 2019; Redfern et al ., 2017), recently referred to as the “quaternary stress response” (Faught et al ., 2020).…”
Section: Global Warming and Fish Stress Physiologymentioning
confidence: 99%
See 1 more Smart Citation
“…The net result of those would depend on the severity of the sustained stressor, but they can have consequences that extend to fish populations (Adams, 1990; Barton, 2002). In addition, prolonged exposure to stress and changes in circulating corticosteroids (mainly cortisol) may have long‐lasting effects on the stress physiology of the organism that influence the coping ability of their progeny (Colson et al ., 2015, 2019; Redfern et al ., 2017), recently referred to as the “quaternary stress response” (Faught et al ., 2020).…”
Section: Global Warming and Fish Stress Physiologymentioning
confidence: 99%
“…Furthermore, warming may particularly affect stenothermal species, typical of tropical or polar latitudes (Comte & Olden, 2017; Somero, 2010). For these species, an inability to tolerate temperature fluctuations and warming might be a particularly life‐threatening challenge (Faught et al ., 2020; Somero, 2010). However, the physiological traits that determine thermal tolerance are not entirely understood.…”
Section: Stress Energy and Global Warming: Potential Consequences For Fish Populationsmentioning
confidence: 99%
“…Metabolic rate can be used to compare the energetic costs of inhabiting different environmental conditions 53,54 , and has been used to compare thermal tolerance, hypoxia, and exposure of foreign compounds 55,56 . Following exposure to an environmental stressor, sh can experience an increase in metabolic rate as part of the secondary stress response, which functions to re-establish homeostasis in the face of environmental challenges 7,57 . McKenzie et al (2007) 53 , for example, showed that resting metabolic rates of European chub (Leuciscus cephalus) increased by about 50% when exposed to polluted river site relative to two cleaner rivers.…”
Section: Discussionmentioning
confidence: 99%
“…Thermal tolerance of rainbow trout (which is sensitive both at extremely high and low temperatures) depends on the genotype, age, stages of development, physical condition, and the history of previous thermal exposure [ 82 , 86 , 87 , 88 , 89 ]. Extreme changes and frequent fluctuations in the temperature of the water affect the endocrine, antioxidant, molecular, immune, and hemato-biochemical functions of rainbow trout [ 41 ], thus, having consequences on the growth of fish, reproduction, metabolism, hemato-physiology, and immunology [ 89 , 90 , 91 , 92 ] ( Figure 5 ).…”
Section: Rainbow Trout Farming Biological Aspects and Effects Of Clim...mentioning
confidence: 99%